Quetiapine-Induced Hypomania and its Association with Quetiapine/Norquetiapine Plasma Concentrations: A Case Series of Bipolar Type 2 Patients - Rovera, C. (Drug Saf Case Rep, 2017)
International guidelines consider quetiapine at medium doses (300–400 mg/day) as valid options for the treatment of bipolar depression for the supposed lower risk of a switch to hypomania/mania than antidepressants. Norquetiapine is an active metabolite with antidepressant action. We describe three cases of induced hypomania in bipolar type 2 subjects who received quetiapine extended-release monotherapy (300 mg/day) for a mild/moderate major depressive episode. Quetiapine and norquetiapine plasma concentrations were measured after 1 week of treatment. Hypomania appeared after 7–10 days of quetiapine extended-release monotherapy and all subjects had a quetiapine/norquetiapine plasma concentration ratio <1. We propose a ratio value <1 as a predictor of risk for a switch to hypomania in bipolar depressed subjects receiving quetiapine extended-release monotherapy. Future research should ascertain the validity of this laboratory parameter to assess the risk of quetiapine-induced hypomania in large samples of bipolar patients.